2019
DOI: 10.3390/su11164423
|View full text |Cite
|
Sign up to set email alerts
|

HR Practices for Supporting Interpersonal Trust and Its Consequences for Team Collaboration and Innovation

Abstract: Innovation fosters sustainable management and allows managers to achieve a competitive advantage. Understanding the mechanisms that explain innovation’s antecedents provides an important contribution to theory and practice. The purpose of this study was to assess the importance of human resources (HR) practices in developing trust-based cooperation, which facilitates organizational innovation. Using the foundation of the Shea and Guzzo model, the roles of HR mechanisms were investigated. This study analyzes ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 124 publications
(134 reference statements)
3
17
0
Order By: Relevance
“…Similarly, social media platforms enhance a sense of community, including feelings of membership, integration, and shared emotional connections (Uysal, 2016). Moreover, an extensive study on human resources practices found links between collaboration, innovation, and trust (Bulińska‐Stangrecka & Bagieńska, 2019). As a ‘venue for social collaboration’ (Uysal, 2016), innovative digital tools can support collaboration and stimulate trust.…”
Section: Discussion Of the Findingsmentioning
confidence: 99%
“…Similarly, social media platforms enhance a sense of community, including feelings of membership, integration, and shared emotional connections (Uysal, 2016). Moreover, an extensive study on human resources practices found links between collaboration, innovation, and trust (Bulińska‐Stangrecka & Bagieńska, 2019). As a ‘venue for social collaboration’ (Uysal, 2016), innovative digital tools can support collaboration and stimulate trust.…”
Section: Discussion Of the Findingsmentioning
confidence: 99%
“…A vast number of studies have confirmed the benefits of trust for sustainable organizational development [8,9]. In terms of talent retention, employee trust has been identified as a positive factor for high organizational commitment [10,11], which predicts a sustainable workforce.…”
Section: Trustmentioning
confidence: 98%
“…On the contrary, the amount of the tax gap, as an accounting category, we are only able to estimate [38]. The absence of a common tax gap definition results in different methodologies for estimating it [39]. The two main methodologies are top-down and bottom-up [40].…”
Section: Literature Reviewmentioning
confidence: 99%